Oxidative stress-mediated beta cell death and dysfunction as a target for diabetes management - Dinić, Svetlana; Arambašić Jovanović, Jelena; Uskoković, Aleksandra; Mihailović, Mirjana; Grdović, Nevena; Tolić, Anja; Rajić, Jovana; Đorđević, Marija; Vidaković, Melita (Frontiers in Endocrinology, 2022)
1 The biggest drawback of a current diabetes therapy is the treatment of the consequences not the cause of the disease. Regardless of the diabetes type, preservation and recovery of functional pancreatic beta cells stands as the biggest challenge in the treatment of diabetes. Free radicals and oxidative stress are among the major mediators of autoimmune destruction of beta cells in type 1 diabetes (T1D) or beta cell malfunction and death provoked by glucotoxicity and insulin resistance in type 2 diabetes (T2D). Additionally, oxidative stress reduces functionality of beta cells in T2D by stimulating their de-/trans-differentiation through the loss of transcription factors critical for beta cell development, maturity and regeneration. This review summarizes up to date clarified redox-related mechanisms involved in regulating beta cell identity and death, underlining similarities and differences between T1D and T2D. The protective effects of natural antioxidants on the oxidative stress-induced beta cell failure ware were also discussed. Considering that oxidative stress affects epigenetic regulatory mechanisms involved in the regulation of pancreatic beta cell survival and insulin secretion, this review highlighted huge potential of epigenetic therapy. Special attention was paid on application of the state-of-the-art CRISPR/Cas9 technology, based on targeted epigenome editing with the purpose of changing the differentiation state of different cell types, making them insulin-producing with ability to attenuate diabetes. Clarification of the above mentioned mechanisms could provide better insight into diabetes etiology and pathogenesis, which would allow development of novel, potentially more efficient therapeutic strategies for the prevention or reversion of beta cell loss.